2023
DOI: 10.1177/17590914231167281
|View full text |Cite
|
Sign up to set email alerts
|

All the PNS is a Stage: Transplanted Bone Marrow Cells Play an Immunomodulatory Role in Peripheral Nerve Regeneration

Gonzalo Piñero,
Marianela Vence,
Marcos L. Aranda
et al.

Abstract: Working on a Wallerian degeneration model in rats, our group has shown the beneficial effects of systemic bone marrow mononuclear cell transplant on morphological and functional parameters, as well as the prevention of neuropathic pain. The current work thus seeks to evaluate the effect of systemic bone marrow cell transplant in a mouse model of sciatic nerve crush and aims to dig deeper into the mechanisms involved in bone marrow cell therapy. Adult C57BL/6J mice were subjected to 8s sciatic nerve crush and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Interestingly, it has been determined that the upregulation of IL-6, IL-1β and TNF-α, among others [56,57], strongly influences neuropathic pain. It may be thus speculated that BMMC relieve neuropathic pain through an immunomodulatory action, previously described by our group, suppressing the expression of several pro-inflammatory cytokines and inducing antiinflammatory cytokines and macrophage phenotype changes [51,58]. Taking in consideration our previous results about cytokine expression and other authors that demonstrated that some chemokines and neuroinflammation signaling are only upregulated in males in terms of neuropathic pain [59][60][61] , in the present manuscript male rats were only evaluated in terms of neuropathic pain.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, it has been determined that the upregulation of IL-6, IL-1β and TNF-α, among others [56,57], strongly influences neuropathic pain. It may be thus speculated that BMMC relieve neuropathic pain through an immunomodulatory action, previously described by our group, suppressing the expression of several pro-inflammatory cytokines and inducing antiinflammatory cytokines and macrophage phenotype changes [51,58]. Taking in consideration our previous results about cytokine expression and other authors that demonstrated that some chemokines and neuroinflammation signaling are only upregulated in males in terms of neuropathic pain [59][60][61] , in the present manuscript male rats were only evaluated in terms of neuropathic pain.…”
Section: Discussionmentioning
confidence: 73%